Preoperative Predictors of Biochemical Recurrence-Free Survival in High-Risk Prostate Cancer Following Radical Prostatectomy - Nkengurutse, Gerard; Tian, Feng; Jiang, Sixiong; Wang, Qi; Wang, Ying; Sun, Weibing (Frontiers in Oncology, 2020)
Background: D’Amico high-risk prostate cancer (Pca) patients experience poor and heterogeneous oncological outcomes. This heterogeneity highlights a need to extensively explore factors associated with poor outcomes to guide decision-making. Objective: To assess predictors of biochemical recurrence (BCR)-free survival in high-risk patients following radical prostatectomy (RP), and subsequently establish a model predicting outcomes. Methods: We retrospectively identified D’Amico high-risk non-metastatic Pca patients who underwent RP between 2013 and 2019 in our hospital. We collected data including PSA level, clinical stage, biopsy Gleason score (GS), number of D’Amico high-risk factors (RF), the inflammatory status (Neutrophil-to-lymphocyte ratio [NLR], derived NLR [dNLR], platelet-to-lymphocyte ratio [PLR] and LDH). Kaplan–Meier methods were used to analyze BCR-free survival. Univariate and multivariate analyses were performed using Cox proportional hazards model to evaluate the association between clinicopathological parameters and BCR-free survival. Results: The median follow-up time for the 101 patients’ cohort was 26 months (range: 3–81 months). The number of RF (1RF vs ≥2RF), biopsy GS (<8 vs ≥8), clinical stage (≤cT2c vs >cT2c), pathological stage and the presence of adverse pathological features were significant predictors of BCR (P<0.05). Other parameters including inflammatory status (dNLR, NLR, PLR, LDH) were not of predictive value. On multivariable analysis, biopsy GS (<8 vs ≥8; HR 2.439) and clinical stage (≤cT2c vs >cT2c; HR 3.271) were the independent predictors of BCR. Based on these 2 independent predictors, patients were stratified into 3 risk subgroups: favorable (0 risk factor; 47% of patients), intermediate (1 risk factor; 42 %), unfavorable (2 risk factors; 11%). The intermediate and unfavorable subgroups have a significantly shorter median BCR-free survival compared to the favorable subgroup (P<0.001). Conclusion: Several factors are associated with BCR. Clinical stage (≤cT2c vs >cT2c) and biopsy GS (<8 vs ≥8) are the independent predictors of BCR. The stratification of high-risk patients into risk subgroups based on these 2 predictors shows that the intermediate and unfavorable subgroups have a significantly shorter median BCR-free survival compared to the favorable subgroup. The preoperative stratification model may help urologists and patients during decision-making. In non-metastatic high-risk patients, preoperative inflammatory markers (NLR, dNLR, PLR, LDH) are not of prognostic value.